2019
DOI: 10.3390/ijms20122861
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin Synthase 2 Promotes Endothelial Dysfunction by Inducing Endoplasmic Reticulum Stress

Abstract: Endothelial dysfunction (ED) is an important contributor to atherosclerotic cardiovascular disease. Our previous study demonstrated that sphingomyelin synthase 2 (SMS2) promotes ED. Moreover, endoplasmic reticulum (ER) stress can lead to ED. However, whether there is a correlation between SMS2 and ER stress is unclear. To examine their correlation and determine the detailed mechanism of this process, we constructed a human umbilical vein endothelial cell (HUVEC) model with SMS2 overexpression. These cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…The gut microbiota–miRNA interactions are involved in the regulation of epithelial dysfunction, which affects the cardiovascular health of the host. Atherosclerosis is the common pathological basis of a variety of cardiovascular and cerebrovascular diseases, and one of the main pathogenic factors is endothelial dysfunction (Rouyer et al 2019 ; Thijssen et al 2019 ; Hua et al 2019 ). Anthocyanins has been reported to extenuate atherosclerosis and promote cholesterol efflux from macrophages (Xia et al 2006 , 2005 ; Tsuda 2012 ).…”
Section: The Gut Microbiota–mirna Interactions In Cardiovascular Disementioning
confidence: 99%
“…The gut microbiota–miRNA interactions are involved in the regulation of epithelial dysfunction, which affects the cardiovascular health of the host. Atherosclerosis is the common pathological basis of a variety of cardiovascular and cerebrovascular diseases, and one of the main pathogenic factors is endothelial dysfunction (Rouyer et al 2019 ; Thijssen et al 2019 ; Hua et al 2019 ). Anthocyanins has been reported to extenuate atherosclerosis and promote cholesterol efflux from macrophages (Xia et al 2006 , 2005 ; Tsuda 2012 ).…”
Section: The Gut Microbiota–mirna Interactions In Cardiovascular Disementioning
confidence: 99%
“…For example, in vivo and in vitro studies demonstrate that saturated fatty acids promote ER stress [ 35 ]. Moreover, our previous results verified that cholesterol deposition could cause endothelial dysfunction by activating ER stress [ 36 , 37 ]. In this study, we proved that tunicamycin-induced ER stress elevated both the cholesterol and triglyceride content in Huh7 and THP-1 cells, and LXR-623 reversed these changes.…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, Zhang et al suggested that lipid rafts provide a platform to inhibit the EGFR regulation of MMP-1 in SiHa cells through the MAPK/ERK signaling pathway [ 36 ]. Therefore, the inhibition of SMS2 activity may affect the SM content in lipid rafts and, thus, inhibit transmembrane signal transduction of the Akt signaling pathway in sperm cells [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SMS activity of sperm was measured as previously described [ 37 , 41 ]. Briefly, sperm were homogenized in a buffer containing 50mM Tris-HCl, 1mM EDTA, and 5% sucrose.…”
Section: Methodsmentioning
confidence: 99%